Identifikasi Jamur pada Beberapa Bumbu Dapur Secara Makroskopis dan Mikroskopis - Rima Paramita, Ni Putu (JURNAL BIOSHELL, 2021)
Fungi are eukaryotic organisms that have spores, are nucleated, do not have chlorophyll, and are threadlike with cell walls composed of cellulose and chitin. Fungi are heterotrophic microorganisms that are saprophytic or parasitic. Fungi have spherical or filamentous cell structures called hyphae. Hyphae are divided into two, namely fertile hyphae which form reproductive cells and upward growth as air hyphae and vegetative hyphae, namely hyphae that seek food into the substrate. Certain conditions, the nature of fungi can turn into pathogens and cause various diseases. Some fungi that contaminate food have the ability to produce toxins or poisons that can cause disease. This research was conducted on samples of garlic, turmeric, chilies, and candlenut which were planted on medium (potato dextrose agar) and incubated for seven days. Observation of fungi growing in each sample was carried out macroscopically and microscopically. Macroscopic observations by observing colony color and colony reverse color, while microscopically observed fungi morphology and hyphae type using a microscope with a magnification of 10 x 40. The identification of funguswas obtained by observing the samples of garlic, turmeric, and candlenut were overgrown with Aspergillus niger. The fungus in the chili sample was Rhizopus stolonifera. Based on these results, it can be conclude that two types of fungi that were found, have different characteristic both macroscopic and microscopic. Keywords: Fungi, macroscopic and microscopic observations, Aspergillus niger, Rhizopus stolonifer.